Transcriptomic and Functional Insights of Calcium Suppresses Grape Berry Cracking: Antioxidant Activation, ABA Pathway Modulation, and VITPL1-Mediated Cell Wall Stability - Shi Hao; Zhou Wen Hua; He Xiao e; Xu Yinyu; Wang Yun (International Journal of Fruit Science)
Calcium treatments are effective in reducing grapevine berry cracking. However, the underlying mechanism of calcium on grapevine berry cracking is not well-known. This work aims to explore the potential molecular mechanism of calcium treatment regulating grapevine berry cracking. 5 g/L of calcium chloride was sprayed at flowering period (A), early (B) and late (C) fruit development period of grapevine, non-calcium sprayed treatment as control (D). The molecular mechanism of calcium treatment on berry skin cracking was studied by RNA-seq. Meanwhile, the key genes [pectin lyase gene (VITPL1)] were analyzed for function verification of overexpression. The other glycan degradation, Peroxisome, Oxidative phosphorylation, Plant hormone signal transduction, and Diterpenoid biosynthesis (p < .05) were directly related to fruit cracking. Meanwhile, 20 genes related to antioxidase were identified, treatment with calcium increased the expression of genes associated with the antioxidant enzyme. Transcripts related to the xanthine dehydrogenase and abscisic aldehyde oxidase (ABA pathway) were found to be down-regulated. 70 genes related to cell wall catabolism were identified, treatment with calcium decreased the expression of genes associated with cell wall catabolism. Furthermore, the VITPL1 gene has a strong effect on grapevine fruit cracking. Calcium treatment significantly reduced the expression level of VITPL1. Calcium can reduce fruit cracking by increasing the level of antioxidant enzyme genes, and decreasing the level of ABA synthesis genes and cell wall catabolism genes (in particular, VITPL1) in the pericarp. Meanwhile, overall A treatment group was the more effective.